2022
DOI: 10.36347/sjams.2022.v10i08.025
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Infection among Children with Nephrotic Syndrome in a Tertiary Level Hospital

Abstract: Background: Patients with nephrotic syndrome are susceptible to numerous bacterial, viral, and fungal infections. To design preventive measures, it is vital to identify the various types of infections, their causative organisms, and sensitivity patterns in the local settings. Methods: From January 2012 to July 2014, this descriptive cross-sectional study was conducted in the Pediatric department of Sir Salimullah Medical College, Mitford Hospital, Dhaka. Children younger than 12 years admitted with nephrotic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…The mean age of children with major infections in NS patients was found to be 6.9 years, which was in concordance with the findings of Gulati et al [ 6 ], Kumar et al [ 14 ], and Lebel et al [ 15 ]. Infective complications were found more in females than in males (1.5:1), which is in concordance with the results of Rahman et al [ 16 ]. The preponderance of females having more infective complications is probably due to the fact that females are at high risk of developing UTI than males, since we observed that UTI was the commonest type of infective complication.…”
Section: Discussionsupporting
confidence: 92%
“…The mean age of children with major infections in NS patients was found to be 6.9 years, which was in concordance with the findings of Gulati et al [ 6 ], Kumar et al [ 14 ], and Lebel et al [ 15 ]. Infective complications were found more in females than in males (1.5:1), which is in concordance with the results of Rahman et al [ 16 ]. The preponderance of females having more infective complications is probably due to the fact that females are at high risk of developing UTI than males, since we observed that UTI was the commonest type of infective complication.…”
Section: Discussionsupporting
confidence: 92%
“…They showed that 67.0% of their study population resided in rural areas which was similar to our study. However, 63.0% of the children came from middle-income families and 27.0% came from low-income families [15]. Another study from Bangladesh showed that, among 50 children, most parents (48%) came from very poor socioeconomic conditions, which was relatable to this study [16].…”
Section: Discussionmentioning
confidence: 68%
“…The top four common infections were intestinal parasitic infection, urinary tract infection, spontaneous bacterial peritonitis, and pneumonia. According to research done in Delhi, India, among hospitalized nephrotic syndrome children aged 1-12 years, the incidence of infection was 43.8%, and peritonitis (24%), pneumonia (18%), and UTI (15%) were the top three types of infection [15]. The other research done in India in hospitalized children aged 1-18 years indicated that the incidence of infection was 29.7%, and UTI and spontaneous bacterial peritonitis were the two common infection types [16].…”
Section: Discussionmentioning
confidence: 99%